2001
DOI: 10.1097/00005792-200103000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Infections in Patients with Immunodeficiency with Thymoma (Good Syndrome)

Abstract: Immunodeficiency with thymoma (Good syndrome, GS) is a rare, adult-onset condition that is characterized by thymoma, hypogammaglobulinemia, and low numbers of peripheral B cells. CD4+ T lymphopenia and an inverted CD4:CD8+ T-cell ratio may be present. Here we report 5 patients with GS and infectious complications who were seen at 3 institutions between 1983 and 1999. Three patients had recurrent sinopulmonary infections, 3 had severe cytomegalovirus (CMV) disease, and 1 had Pneumocystis carinii pneumonia. Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
227
0
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(247 citation statements)
references
References 50 publications
7
227
0
13
Order By: Relevance
“…Pure red cell aplasia and myasthenia gravis are common complications of thymoma, and improvement of these complications is often observed after thymectomy. However, Good syndrome is occasionally progressive even after thymectomy and/or corticosteroid treatment (2). In the present case, the patient's pure red cell aplasia and myasthenia gravis had been controlled after thymectomy and subsequent corticosteroid treatment, but hypoglobulinemia and recurrent lower respiratory tract infections were persistent.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Pure red cell aplasia and myasthenia gravis are common complications of thymoma, and improvement of these complications is often observed after thymectomy. However, Good syndrome is occasionally progressive even after thymectomy and/or corticosteroid treatment (2). In the present case, the patient's pure red cell aplasia and myasthenia gravis had been controlled after thymectomy and subsequent corticosteroid treatment, but hypoglobulinemia and recurrent lower respiratory tract infections were persistent.…”
Section: Discussionmentioning
confidence: 49%
“…While the symptoms of pure red cell aplasia and myasthenia gravis, which often occur with thymoma, are generally improved by thymectomy, Good syndrome is believed to be progressive even when thymectomy and/or corticosteroid treatment are applied (2). We herein report a case of Good syndrome that showed recurrent lower respiratory tract infections beginning nine months after a thymectomy, with chest computed tomography (CT) findings similar to diffuse panbronchiolitis (DPB).…”
Section: Introductionmentioning
confidence: 94%
“…The most commonly documented infectious complications in patients with thymoma with immunodeficiency include recurrent upper and lower respiratory tract infections with encapsulated organisms [1]. The patient also had chronic diarrhea, another common feature of thymoma with immunodeficiency, being reported in approximately half of the patients with this primary immunodeficiency.…”
Section: Discussionmentioning
confidence: 94%
“…Search terms included: "Good('s) syndrome", "thymoma with immunodeficiency", "thymoma", "hypogammaglobulinemia", "HSV" or "disseminated HSV". Additional cases were identified through an extended review of all the pathogens reported in 51 patients with thymoma with immunodeficiency, from 1966 to 1999 [1][2][3][4][5][6]. Reports of HSV-related infections were included if they occurred in patients with documented thymoma and hypogammaglobulinemia and/or B-cell lymphopenia [1].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation